1999
DOI: 10.1108/14634449910271410
|View full text |Cite
|
Sign up to set email alerts
|

The role of social process in participative decision making in an international context

Abstract: If participation is to be a reality, the institution of appropriate structures is not enough ‐ the social processes within these must also facilitate power sharing. In an international context, national cultures will have different effects on social process. The attitudes of managers towards aspects of decision making in their organizations, and their own behaviour, characterise the social process. Organizational characteristics concerning information sharing and manipulation, decision style, and the role of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Nigerian and American employees in these organizations with similar task responsibilities may experience similar levels of PDM. Social influences among employees may in turn create employee expectations and desires for PDM among these Nigerian and American workers that are very similar despite differences in their cultural norms (Ryan, 1999). In this research, the institutionalized similarities in management approaches across the public sector organizations studied may present a ''strong'' situation in which we examine the effects of cultural differences on the relationship of PDM with employee organizational commitment (as detailed in a previous study).…”
mentioning
confidence: 94%
“…Nigerian and American employees in these organizations with similar task responsibilities may experience similar levels of PDM. Social influences among employees may in turn create employee expectations and desires for PDM among these Nigerian and American workers that are very similar despite differences in their cultural norms (Ryan, 1999). In this research, the institutionalized similarities in management approaches across the public sector organizations studied may present a ''strong'' situation in which we examine the effects of cultural differences on the relationship of PDM with employee organizational commitment (as detailed in a previous study).…”
mentioning
confidence: 94%
“…While participatory decision-making is a fundamental principle of most community coalitions, the empirical research on participatory decision-making is found primarily within the literatures on business management, industrial organizational behavior, and public and human services administration (Black & Gregersen, 1997;Lam, Chen, & Schaubroeck, 2002;Miller & Monge, 1987;Ramsdell, 1984;Ryan, 1999;Schwartz, Gottesman, & Perlmutter, 1988;Stohl & Cheney, 2001). Within these fields the process of participatory decision-making is described as consisting of fundamental components including problem identification, generating alternative solutions, choosing a solution, planning the implementation, and evaluating results (Locke & Schweiger, 1979;Margulies & Black, 1987).…”
Section: Administration In Social Workmentioning
confidence: 99%
“…Within these settings the most basic elements of effective decision-making for task groups have been identified as setting a clear agenda, providing participants with information with which to make informed decisions, specifying implementation tasks, and assigning personnel responsibility for implementation (Barkan, 2002;Bradford, 1976;Carnes, 1980;Frank, 1989;Jay, 2003;Kieffer, 1988;Thomsett, 1989). Research has also examined how participation and decision-making processes vary on dimensions including the procedures governing task groups, the nature of the decision topic, the degree of topical knowledge among participants, and the organizational rationale for encouraging participation (such as furthering democratic values or enhancing employee's performance) (Cotton, et al, 1988;Dachler & Wilpert, 1978;Lam, Chen, & Schaubroeck, 2002;Ryan, 1999;Schreiber, 1996).…”
Section: Administration In Social Workmentioning
confidence: 99%
“…direct assessment versus elicitation of tradeoffs), and (v) the extent to which the method accommodates different perspectives and problem structures. Detailed discussions about the strengths and flaws associated with specific decision methods can be found elsewhere (Bell and Sheail, 2005;Berthoz, 2004;Eisenfuehr and Weber, 2003;French, 1995;Kangas and Kangas, 2004;Larichev, 1992;Liljas and Blumenschein, 2000;Mingers and Rosenhead, 2004;Poyhonen and Hamalainen, 2001;Ryan, 1999;van den Bergh et al, 2000). Which method is more appropriate depends on the set of assumptions that seems most valid for a given situation and person, or group of people -the choice of method is in fact frequently influenced by the beliefs of those identifying policy options.…”
Section: Decision Analysis and Supportmentioning
confidence: 99%